Can reticulocyte parameters be of use in detecting iron deficient erythropoiesis in female athletes? - Ashenden, M. J.; Pyne, D. B.; Parisotto, R.; Dobson, G. P.; Hahn, A. G. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: The purpose of this study was to investigate whether monitoring reticulocyte profiles, which are known to respond to iron store depletion in sedentary populations, could also be utilised with intensely training athletes. METHODS: A retrospective study of blood samples from 134 national level athletes (61 males, 73 females) at the Australian Institute of Sport were analysed, from which reference ranges were calculated. To ascertain the stability of reticulocyte profiles during periods of intense physical training, the intra-individual variation of these parameters in 12 iron-replete female athletes over a four month period of training was documented. The precision with which the analyzer measured these parameters was also determined using duplicate samples from 37 female athletes. To establish whether reticulocyte parameters were sensitive to iron deficient erythropoiesis in athletes, reticulocyte profiles of five female athletes diagnosed by medical personnel as having depleted iron stores were compared before and after iron therapy to seven controls. RESULTS: Corpuscular hemoglobin concentration mean (CHCMr) and mean corpuscular volume (MCVr) showed little variation over time in iron-replete females, with 95% of all fluctuations being within 5.8% and 4.3% of original values, respectively. Iron supplementation in athletes with depleted iron stores elicited an increase in CHCMr (p = 0.01), and a decrease in the distributions of reticulocyte volume (RDWr, p = 0.01) and cell hemoglobin concentration (HDWr, p < 0.01). The ratios of reticulocyte to mature cell MCV (p < 0.01) and CHCM (p < 0.01) also changed following iron therapy. No such changes occurred in non-supplemented controls with normal iron stores. CONCLUSIONS: These data lend support to the thesis that monitoring of reticulocyte parameters can be of use in detecting iron deficient erythropoiesis in female athletes.